2016
DOI: 10.1155/2016/2734139
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 670 nm Light Therapy to Protect against Photoreceptor Cell Death Is Dependent on the Severity of Damage

Abstract: Photobiomodulation at a wavelength of 670 nm has been shown to be effective in preventing photoreceptor cell death in the retina. We treated Sprague-Dawley (SD) rats with varying doses of 670 nm light (9; 18; 36; 90 J/cm2) before exposing them to different intensities of damaging white light (750; 1000; 1500 lux). 670 nm light exhibited a biphasic response in its amelioration of cell death in light-induced degenerationin vivo. Lower light damage intensities required lower doses of 670 nm light to reduce TUNEL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Our data showed that PBM at all wavelengths upregulated both maximal and basal respiratory rates, ATP production and spare respiratory capacity (the amount of extra ATP produced through oxidative phosphorylation available in the case of an increase in energy demand ) in myotubes (Figure , P < 0.05), whilst these were only upregulated at a wavelength of 810 nm from myoblasts ( P < 0.05). Comparatively, previous studies exploring the effects of PBM using a Seahorse analyser only explored the effects of red light (635‐700 nm) and only Chu‐Tan et al found PBM modulated real‐time mitochondrial activity . Data from this study suggest that mitochondrial content may influence cellular response to PBM.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…Our data showed that PBM at all wavelengths upregulated both maximal and basal respiratory rates, ATP production and spare respiratory capacity (the amount of extra ATP produced through oxidative phosphorylation available in the case of an increase in energy demand ) in myotubes (Figure , P < 0.05), whilst these were only upregulated at a wavelength of 810 nm from myoblasts ( P < 0.05). Comparatively, previous studies exploring the effects of PBM using a Seahorse analyser only explored the effects of red light (635‐700 nm) and only Chu‐Tan et al found PBM modulated real‐time mitochondrial activity . Data from this study suggest that mitochondrial content may influence cellular response to PBM.…”
Section: Resultsmentioning
confidence: 51%
“…Subsequently, Seahorse assay technology was utilised to explore the effect of a series of wavelengths on real‐time mitochondrial respiration. Whilst several studies have explored the effect of specific PBM parameters utilising Seahorse technology , ours is the first that has explored an array of wavelengths and in particular the use of blue light in PBM. Our data showed that PBM at all wavelengths upregulated both maximal and basal respiratory rates, ATP production and spare respiratory capacity (the amount of extra ATP produced through oxidative phosphorylation available in the case of an increase in energy demand ) in myotubes (Figure , P < 0.05), whilst these were only upregulated at a wavelength of 810 nm from myoblasts ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no comprehensive data to correlate the improvement in the severity of brain disorders and effective PBM therapy protocols, studies on the use of this therapy for treatment of MDD patients suggest that the successful outcomes largely depend on the delivered dosage, number of sessions, treatment intervals, as well as the total length of the treatment program [203,222]. These criteria have been confirmed by other studies [223,224] that reported the effectiveness of the PBM therapy was not only affected by dosage, but also the initial severity of the damage affected the treatment outcomes. It should be noted that there is a real risk of overtreatment if too much light is delivered either too quickly or too often [257].…”
Section: Influence Of Irradiation Parameters In Brain Pbm Therapymentioning
confidence: 71%
“…Several studies with albino rats, which have been exposed to additional oxidative stress, demonstrate several beneficial effects of red LED-light with 670 nm (see Table 1): The induced histopathologic alterations could be attenuated and the retinal cells were stabilised and protected against light-induced damage. The beneficial effect of red light was present, regardless of whether it was applied before, during or after a detrimental intense white light exposition (Albarracin, Eells, and Valter, 2011;Chu-Tan et al, 2016).…”
Section: Photobiomodulation (Pbm) and Amdmentioning
confidence: 99%